Negotiorum gestio in South African law : an historical and comparative analysis - Van Zyl, Deon Hurter (Department of Private Law, 2023)
The present treatise deals with the subject of negotiorum gestio, or unauthorised administration of the affairs of another, as it is developed and been applied in South African law. As appears from the tittle hereof, it is not merely a description of the relevant aspects of negotiorum gestio as applied in modern South African practice, but an historical and comparative analysis of an institution which has its origin in classical Roman Law and has experienced fruitful development over a period of approximately two thousand years. In this regard the historical method of research has been applied, commencing with the Roman origins, continuing with the medieval and later development and concluding with relevant law as applied in South Africa up to the present day.